An Analysis of Good Corporate Governance Implementation According to the Zakat Core Principle in LAZNAS XXX - Farid Suprayogo, Fajar; Ajeng Kartika Galuh (Islamic Economics and finance in Focus, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) based on the Zakat Core Principle at XXX in Kota Malang, which faces challenges in maintaining public trust through transparency and accountability. Using a descriptive qualitative method with observations and interviews from five key informants, the study found that the implementation of GCG principles at XXX is relatively good, although the understanding of the Zakat Core Principle is not yet fully optimal. The application of GCG principles, including transparency, accountability, responsibility, independence, and fairness, has increased public trust in the institution. The study concludes that XXX has successfully implemented GCG practices and recommends further training to enhance understanding of the Zakat Core Principle to ensure that the amil governance system operates more effectively in accordance with existing regulations.